(ISC)2 CISSP official study guide - Chapple, Mike; Stewart, James Michael; Gibson, Darril (Sybex, 2018)
CISSP (ISC)2 Certified Information Systems Security Professional Official Study Guide, 8th Edition has been completely updated for the latest 2018 CISSP Body of Knowledge. This bestselling Sybex study guide covers 100% of all exam objectives. You'll prepare for the exam smarter and faster with Sybex thanks to expert content, real-world examples, advice on passing each section of the exam, access to the Sybex online interactive learning environment, and much more. Reinforce what you've learned with key topic exam essentials and chapter review questions.